Labour legislation in Emfuleni's domestic worker sector: awareness and compliance - Marais, Christel (My University, 2013)
Sectoral Determination 7: Domestic Worker Sector was proclaimed by the Minister of Labour, Membathisi Mdladlana, and has stipulated the minimum employment conditions for the domestic worker sector since 1 September 2002. The purpose of this study evolved from the problem statement which clearly indicated the need for the assessment of awareness and compliance within the domestic worker sector. A detailed literature review enabled the researcher's orientation to the historical context of the sector as well as the need for transformation. Ultimately, the Determination's stipulations guided the assessment of both awareness (knowledge) and compliance (actions that correspond with legislative obligations) during an empirical review. A survey design was used to obtain responses from both domestic workers and employers of domestic workers, who were not necessarily in a direct employment relationship, within the Emfuleni Local Municipal District. Collected data was statistically captured and analysed. Desc1iptive statistics indicated that both employers and domestic workers have limited awareness with regard to the stipulations of Sectoral Determination 7. Results further indicated the difficulty in making a general pronouncement regarding compliance levels. It is suggested that compliance should be considered per individual stipulation of the Determination. The study concludes with the researcher's recommendation that more must be done to raise awareness within the sector amongst both employers of domestic workers and domestic workers. It was also recommended that more labour inspectors be made available not only to ensure the enforcement of Sectoral Dete1mination 7 (compliance) but also to facilitate the creation of continuous awareness.
Thesis (M. Tech. (Labour Relations Management)--Vaal University of Technology
Keywords: Domestic workers; Minimum employment conditions; Sectoral Determination 7; 344.6801; Domestics -- Employment -- South Africa; Contract labor -- South Africa; Labor laws and legislation -- South Africa